Colorado professor wins Templeton Religion Prize - Stammer, Larry B., author; Times-Mirror Co., publisher (Colorado State University. Libraries, 2003)
Holmes Rolston, III, whose explorations of faith and science have helped foster religious interest in the environment, has been awarded the 2003 Templeton Prize. Rolston has argued that humans must be seen as part of, and not apart from, the natural world. The crisis of the environment is essentially a crisis of spirit.
Keywords: philosophy professor; Colorado State University; Templeton Prize; Rolston, Holmes, 1932-2025